An investigation into effect of sawdust treatment on permeability and compressibility of soil-bentonite slurry cut-off wall - Keramatikerman, Mahdi; Chegenizadeh, Amin; Nikraz, Hamid (Elsevier, 2017)
Landfills containing municipal solid waste (MSW) are increasing with growing population and consumption rate in Australia. However, construction of conventional containment systems such as slurry walls are a cost-effective and timesaving approach to control the leachate diffusion, they are weak barriers when exposed to volatile organic compounds (VOCs) or heavy metals, which are abundant in municipal solid wastes. This study investigates effect of sawdust addition on hydraulic conductivity and compressibility of the Soil-Bentonite (SB) slurry cut-off wall. A series of hydraulic conductivity and consolidation tests performed on SB backfill amended with 2%, 5% and 10% sawdust contents. The results showed that application of sawdust reduced the final hydraulic conductivity (kf) in the range of 2.13 × 10−10 ≤ kf ≤ 3.5 × 10−10 m/s. The computed hydraulic conductivity values using consolidation theory (ktheory) also showed an identical decreasing trend in the range of 5.10 × 10−11 ≤ ktheory ≤ 3.50 × 10−10 m/s under 24 ≤ σ′n ≤ 1280 kPa effective overburden pressure (σ′n). The coefficient of consolidation (cv) was computed using Casagrande and Taylor methods showed a good agreement range value. Additionally, the computed compression index (Ci) and swelling index (Cs) were calculated using void ratio and effective overburden pressure graphs (e - logσ′n) showed that application of sawdust had no significant impact on settlement of the SB backfill.